Comparative Transcriptome Profiling of Virulent and Attenuated Ehrlichia ruminantium Strains Highlighted Strong Regulation of map1- and Metabolism Related Genes - Pruneau, Ludovic; Lebrigand, Kevin; Mari, Bernard; Lefrançois, Thierry; Meyer, Damien F.; Vachiery, Nathalie (Frontiers in Cellular and Infection Microbiology, 2018)
The obligate intracellular pathogenic bacterium, Ehrlichia ruminantium, is the causal agent of heartwater, a fatal disease in ruminants transmitted by Amblyomma ticks. So far, three strains have been attenuated by successive passages in mammalian cells. The attenuated strains have improved capacity for growth in vitro, whereas they induced limited clinical signs in vivo and conferred strong protection against homologous challenge. However, the mechanisms of pathogenesis and attenuation remain unknown. In order to improve knowledge of E. ruminantium pathogenesis, we performed a comparative transcriptomic analysis of two distant strains of E. ruminantium, Gardel and Senegal, and their corresponding attenuated strains. Overall, our results showed an upregulation of gene expression encoding for the metabolism pathway in the attenuated strains compared to the virulent strains, which can probably be associated with higher in vitro replicative activity and a better fitness to the host cells. We also observed a significant differential expression of membrane protein-encoding genes between the virulent and attenuated strains. A major downregulation of map1-related genes was observed for the two attenuated strains, whereas upregulation of genes encoding for hypothetical membrane proteins was observed for the four strains. Moreover, CDS_05140, which encodes for a putative porin, displays the highest gene expression in both attenuated strains. For the attenuated strains, the significant downregulation of map1-related gene expression and upregulation of genes encoding other membrane proteins could be important in the implementation of efficient immune responses after vaccination with attenuated vaccines. Moreover, this study revealed an upregulation of gene expression for 8 genes encoding components of Type IV secretion system and 3 potential effectors, mainly in the virulent Gardel strain. Our transcriptomic study, supported by previous proteomic studies, provides and also confirms new information regarding the characterization of genes involved in E. ruminantium virulence and attenuation mechanisms.